2002
DOI: 10.1124/mol.62.5.1036
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Hydrophobic Domain of Polymyxin B Nonapeptide: Effect on Outer-Membrane Permeabilization and Lipopolysaccharide Neutralization

Abstract: Polymyxin B nonapeptide (PMBN), a cationic cyclic peptide derived from the antibacterial peptide polymyxin B, is capable of specifically increasing the permeability of the outer membrane (OM) of Gram-negative bacteria toward hydrophobic antibiotics. In this study, we evaluated the contribution of the hydrophobic segment of PMBN (i.e., D

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 29 publications
4
54
2
Order By: Relevance
“…Many excellent reports that provide insight into the importance of peptide sequences and structures in antimicrobial activity have been published (for a review see reference 23). In several cases, it has been demonstrated that antimicrobial activity does not correlate with binding affinity (25,27). When binding affinity and antimicrobial activity are not interrelated, the peptide often binds to the membrane with high affinity but lacks the ability to exhibit antimicrobial activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many excellent reports that provide insight into the importance of peptide sequences and structures in antimicrobial activity have been published (for a review see reference 23). In several cases, it has been demonstrated that antimicrobial activity does not correlate with binding affinity (25,27). When binding affinity and antimicrobial activity are not interrelated, the peptide often binds to the membrane with high affinity but lacks the ability to exhibit antimicrobial activity.…”
Section: Discussionmentioning
confidence: 99%
“…More likely, differences in cell surface chemistry between the two strains of E. coli were responsible for the specific binding. Studies of the surface localization of outer membrane constituents indicate that lipopolysaccharide is the most likely site of antimicrobial peptide binding (17,20,27). Lipopolysaccharide is an amphipathic molecule with a hydrophobic, well-conserved lipid A region and a highly variable hydrophilic region.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, total or semisynthesis or modifications of polymyxins was performed chemically or enzymatically, and the resulting products were effectively used for structure-function study (6,20,36,45,50,52). There is a limitation to obtaining diverse derivatives by using chemical or enzymatic approaches, however, and this limitation is related to the structural complexity of polymyxin.…”
mentioning
confidence: 99%
“…Most of the iron-independent antibacterial activity of Lf is concentrated into a cluster of positively charged residues near the N-terminus of the Lfs from many mammalian species [40][41][42][43]. This positive cluster binds to the lipid A part of LPS molecules present on the outer membrane of clinically relevant bacterial species [44,45], acting therefore in a way similar to that of a number of polycationic compounds, such as polymyxin B nonapeptide [46]. In addition, following the observation that LPS release induced by Lf is neutralised by high calcium concentration in the medium, Ellison et al [47] hypothesised that Lf could be broadly active as a calcium chelator such as EDTA, which is known to induce LPS release [48].…”
Section: Bactericidal Activity Not Related To Iron Withholdingmentioning
confidence: 99%